Implementasi Diagram Tree pada Rancang Bangun Sistem Informasi Bebayuhan Oton Berbasis Web - Dewi, Ni Putu Ratna Gangga; Sudana, Oka; Sukarsa, Made (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 3 Desember 2017, 2017)
Bebayuhan Oton is a ceremony that is believed to Hindu in Bali can neutralize the negative influence of someone's birth day including the character, nature and behaviour according to the Balinese Calendar. This ceremony uses a kind of upakara (ceremony tools and equipment) called banten. Banten bayuh oton or bayuh oton ceremony equipments can be knownby asking bayuh oton expert or Sulinggih (Religious Leader in Bali). However, the time needed to prepare this ceremony is less effective and efficient. The reason is the difficulty of arranging the meeting time with the Sulinggih and the lack of knowledge about bayuh oton ceremony, so it needed an application that can facilitate the search of information related to bayuh oton ceremony also can be used as guidance in the implementation of the ceremony. The information system about bebayuhan was built to facilitate Hindus' community to obtain information about bebayuhan oton. The modeling system used is a tree diagram to connect the procession of bebayuhan oton ceremony with banten and other necessary tools. This system displays the data including the procession, banten as well as the facilities as a complement ceremony